Advances in our understanding of the pathogenesis of glomerular thrombotic microangiopathy - Keir, Lindsay (Springer-Verlag, 2010)
Glomerular thrombotic microangiopathy is a hallmark feature of haemolytic uraemic syndrome, the leading cause of acute renal failure in childhood. This paper is a review of the different mechanistic pathways that lead to this histological picture in the kidney. It will focus on atypical HUS and complement dysregulation, but will also highlight some other recent advances in our understanding of this condition, including the potential role of the molecule vascular endothelial growth factor- A (VEGF-A).